PENGARUH PENERAPAN MANAJEMEN RISIKO BISNIS DALAM SMALL BUSINESS DEVELOPMENT PADA WARKOP 96 - Lilis Lilis; Novia Clarissa; Herliani Herliani; Dikson Dikson; Jhon Wilson (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Warkop96 has a unique concept where food is served with large and attractive portions. At the beginning of the opening of this warkop96 business, consumers were very interested in visiting warkop 96. The purpose of the study was to determine the effect of implementing Business Risk Management in Small Business Development. The methods used are qualitative methods and survey methods. Based on this research, it can be seen that in the strategy planned by Warkop96 there are several risk assessments that must be analyzed by Warkop 96, namely by analyzing the strengths, weaknesses, opportunities, and threats (SWOT).